Efetividade dos termos de ajuste de conduta firmados pelo Ministério Público do Trabalho: uma análise empírica - Souza, Ilan Fonseca de (2016)
The terms of conduct adjustment (TACs) have been the main performance instrument used by the Labour Prosecutors. For this reason, this research aims to assess its effectiveness, in other words, whether they are being met by employers. After review of the literature that extols the advantages of extrajudicial instrument, perform critical of the arguments used, and we present premises for the TACs have a higher rate compliance. In order to test these theoretical assumptions, in addition to the review of pre-existing investigations in some sectors and regions of Brazil, we conducted empirical research in São Paulo (Attorney Labor Regional of the 2nd and 15th Region) and found a high dropout rate to obligations set out in TACs, verging on 60% of noncompliance determined, even at short term, few clauses, and surface inspections of the agreements. Identified all TACs executed in this state in 2013, we analyze their content using internal system of work of the prosecution entitled "Digital MPT". We concluded by an inability of the current dynamics of the TAC to achieve their goals, and a pattern of recalcitrance of employers before adjustments.